SMEs' PERFORMANCE IMPROVEMENT IN NON-AGRICULTURAL PRODUCTION THROUGH FINANCIAL LITERACY MEDIATION BY EXTERNAL FUNDING ACCESS IN JEPARA, INDONESIA - Khajar, Ibnu; Ghoniyah, Nunung (Jurnal Aplikasi Manajemen, 2022)
SMEs have contributed to labor absorption and the province's budget. However, SMEs face significant obstacles in accessing external funding. They also have a weak understanding of various financial aspects. This study aims to examine the effect of financial literacy and external funding access on the growth of SMEs. The sample population comprised SMEs in the non-agricultural sector in Jepara, Indonesia, Central Java Province. This study employed PLS-SEM statistical tools to prove the hypotheses and answer the research objectives. The study indicated that financial literacy could improve access to external funding sources, enhancing the growth of SMEs. However, financial literacy had no significant positive effect on the development of SMEs. This study also proved complete mediation with external funding as the mediator. This study is expected to be an essential reference and recommendation for reducing the unemployment rate. Additionally, it increases the prosperity and welfare of the people in Central Java Province through the establishment and development of SMEs and government policies to further intensify the program.